2019
DOI: 10.1111/vsu.13216
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection associated with equine orthopedic internal fixation: 155 cases (2008–2016)

Abstract: Objective To determine the prevalence of surgical site infection (SSI) after internal fixation and to identify risk factors for SSI and nonsurvival. Study design Retrospective study. Animals One hundred fifty‐five horses with long bone fractures or arthrodesis treated by internal fixation at 1 hospital between 2008–2016. Methods Signalment, diagnosis, surgical repair, surgeon, surgical time, antimicrobial use, SSI onset, bacterial identification, and adjunct treatments were recorded. Perioperative variables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 24 publications
3
57
2
1
Order By: Relevance
“…HIV patients have low or even reduced immunity and a higher risk of opportunistic infections [24]. More and more complex internal fixations were likely to cause infection of the incision, and the disturbance to the physiological function of the body is also large, which could active the inflammatory system [25]. When the acute inflammation occurred, blood acutephase reactant increased rapidly, including α-antirypsin, α2-mactoglobulin, C reactive protein, haptoglobin, transferrin, fibrinogen, etc.…”
Section: Discussionmentioning
confidence: 99%
“…HIV patients have low or even reduced immunity and a higher risk of opportunistic infections [24]. More and more complex internal fixations were likely to cause infection of the incision, and the disturbance to the physiological function of the body is also large, which could active the inflammatory system [25]. When the acute inflammation occurred, blood acutephase reactant increased rapidly, including α-antirypsin, α2-mactoglobulin, C reactive protein, haptoglobin, transferrin, fibrinogen, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, the details and protocol for A-RLP were not reported and the selection of cases for A-RLP was based on the individual case and attending surgeon's preference. The same clinician group from the same equine hospital have subsequently produced another similar retrospective study, recently (Curtiss et al 2019), where they retrospectively reviewed the records of 155 cases undergoing internal fixation. They found a postoperative orthopaedic infection rate of 14.2%, which was much lower than in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Similarly, surgical site infections (SSIs) associated with fracture repair, exploratory laparotomies, and arthroscopy can result in substantial complications with significant implications for both the patient and owner, including delayed healing and increased hospitalization, and may become a limiting factor in successfully treating these cases. [2][3][4][5] Pathogenic bacteria in equine wounds and infected surgical sites have been categorized in multiple studies spanning the last 30 years. A study by Schneider et al 2 looked at 192 horses with septic arthritis/tenosynovitis, and as part of that study they reported the culture results of 156 horses and found that Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…1 Involvement of underlying synovial structures or bones is not uncommon and complicated infections can lead to increased morbidity and mortality in such cases. [2][3][4] Similarly, surgical site infections (SSIs) associated with fracture repair, exploratory laparotomies, and arthroscopy can result in substantial complications with significant implications for both the patient and owner, including delayed healing and increased hospitalization, and may become a limiting factor in successfully treating these cases. [2][3][4][5] Pathogenic bacteria in equine wounds and infected surgical sites have been categorized in multiple studies spanning the last 30 years.…”
Section: Introductionmentioning
confidence: 99%